Use of the infusion of Sonchus oleraceus leaves for the treatment of vitiligo (Research, Society and Development, 2021)
Objective: To describe the results of using the infusion of Sonchus oleraceus leaves for the treatment of vitiligo. Method: Qualitative study, carried out in a border municipality in the State of Paraná, in the second half of 2019 and early 2020, with individuals who used the infusion of Sonchus oleraceus. A semi-structured instrument was used with questions regarding the use of that plant. Interviews were conducted, with thematic analysis of the results. Results: Participants were 11 individuals with vitiligo, seven women and four men, aged between 25 and 61 years (mean of 42 years), with depigmentation in various regions of the body. They used the infusion of the leaves of Sonchus oleraceus in the period from 3 to 13 months (average of 9 months), and prepared the tea with 5 leaves in a liter of water, consuming an average of 700 mL a day. Most individuals observed pigmentation in depigmented areas. The pigmentation of the areas was observed between 3 and 6 months after the start of the infusion (mean of 4 months). Related to the disease, the participants expressed sadness, boredom and difference, with a direct impact on daily life, but with the improvement after the use of the plant, happiness and satisfaction opened up space for a new life. Conclusion: The infusion of Sonchus oleraceus caused the pigmentation of white spots in patients with vitiligo, and the results of herbal therapy gave positive feelings to the participants.